Austroborus cordillerae (Mollusca: Gastropoda) from central Argentina: a rare, little-known land snail - Gordillo, Sandra (2021)
In the central region of Argentina, there is a diverse land snail fauna dominated by endemic species. Among them, Austroborus cordillerae (Doering) is a little-known species that could be on the verge of extinction. This work therefore provides updated information on the records of shells by incorporating new field findings.